Mechanical outcome of accelerated corneal crosslinking evaluated by Brillouin microscopy. Issue 11 (November 2017) - Webb, Joshua N.; Su, Johnny P.; Scarcelli, Giuliano
Abstract : Purpose : To quantify corneal mechanical changes induced by corneal crosslinking (CXL) procedures of different ultraviolet‐A (UVA) intensity and exposure time using Brillouin microscopy. Settings : University of Maryland, College Park, Maryland, USA. Design : Experimental study. Methods : Porcine cornea samples were debrided of epithelia and soaked with riboflavin 0.1% solution. Samples were exposed to a standard 5.4 J/cm 2 of UVA radiation with varying intensity and exposure time as follows: 3 mW/cm 2 for 30.0 minutes, 9 mW/cm 2 for 10.0 minutes, 34 mW/cm 2 for 2.65 minutes, and 50 mW/cm 2 for 1.80 minutes. Using Brillouin microscopy, the Brillouin modulus for each sample was computed as a function of radiation intensity/exposure time. For validation, the Young's modulus was found with the stress–strain test and compared at each irradiation condition. Results : The standard 3 mW/cm 2 irradiance condition produced a significantly larger increase in corneal Brillouin modulus than the 9 mW/cm 2 ( P ≤ .05), 34 mW/cm 2 ( P ≤ .01), and 50 mW/cm 2 ( P ≤ .01) conditions. Depth analysis showed similar anterior sections of the standard and 9 mW/cm 2 conditions but significantly less stiffening in the central and posterior of the 9 mW/cm 2 condition. The stiffening of the standard protocol was significantly larger in all sections of the 34 mW/cm 2 and 50 mW/cm 2 conditions ( P ≤ .01). The overall change in Brillouin‐derived Brillouin modulus correlated with the increase in Young's modulus ( R 2 = 0.98). Conclusions : At a constant UVA light dose, accelerating the irradiation process decreased CXL stiffening. Brillouin analysis showed that accelerated protocols were especially ineffective in the deeper portions of the cornea.